Consumer culture theory - Thyroff, Anastasia E., 1986-; Murray, Jeff B.; Belk, Russell W. (Bingley, U.K. : Emerald, 2015)
The chapters in this volume are selected from the best papers presented at the 10th Annual consumer culture theory conference held at the University of Arkansas, USA in June 2015. The diverse interpretive research and theory represented in this volume provides the reader with intellectually stimulating opportunities to examine the intersections between a variety of topics that represent the cutting edge in consumer research. These studies draw on an array of qualitative methodologies and the substantive topics represent crucial issues for our times.
Introduction : consumer culture theory : ten years gone (and beyond) / Eric J. Arnould, Craig J. Thompson -- Chaosmosis : French thought styles and the possible reactivation of consumer culture theory / Benoi<U+0302>t Heilbrunn -- Roots and development of consumer culture theory / Sidney J. Levy -- Consumer culture theory and the AMA job market : understanding the challenges and crafting winning strategies / Laurel Steinfield, Henri Weijo -- Critical theory in consumer research : advancing the conversation / Amanda Earley -- Critical regionalities : re-thinking regions in CCT / Jessica Chelekis, Bernardo Figueiredo -- The formation of consumer activism : context and meanings of an activist order / Ahmed Benmecheddal, Nil O<U+0308>zc<U+0327>aglar-Toulouse -- Chronos and Kairos : multiple futures and damaged consumption meaning / Thomas Derek Robinson -- Of gates and doors : a critical reflection on agency / Karen V. Fernandez -- The peril of pink bricks : gender ideology and Lego friends / Gry Hngsmark Knudsen, Erika Kuever -- Myth-mediated branding / Jack S. Tillotson, Diane M. Martin -- Memories standing outside of the self : the commodity, the collector, and Walter Benjamin's theory of experience / Murray Skees -- Connoisseurship taste ritual / Ronan Quinta<U+0303>o, Eliane P. Zamith Brito -- Ambiguity and fandom : the (meaningless) consumption and production of popular culture / Clinton D. Lanier Jr., C. Scott Rader, Aubrey R. Fowler III -- "They're taking us for fools" : when ethnic spectacles are perceived as dystopias / Fatima Regany, Julie Emontspool -- Resolving contradictions in human brand celebrity and iconicity / Toni Eagar, Andrew Lindridge -- Sensory identity : the impact of olfaction on consumption / Samantha N.N. Cross, Meng-Hsien (Jenny) Lin, Terry L. Childers -- Negotiating identity reconstruction through consumption : an analysis of the experiences of consumers with acquired sensory impairments / Anthony Beudaert, Nil O<U+0308>zc<U+0327>aglar-Toulouse, Meltem Tu<U+0308>re -- "There will not be a World Cup" : the Kratophanous power of the FIFA 2014 World Cup in Brazil / Benjamin Rosenthal, Flavia Cardoso -- Taking off our earrings and staying out of jail : black women and Madea on Tyler Perry's Chitlin' Circuit / Adrienne Lotson.
Print version record
Keywords: Business & Economics -- Marketing -- General; Behavioural theory (Behaviourism); Consumption (Economics) -- Congresses; Consumption (Economics) -- Social aspects -- Congresses; Consumer behavior -- Congresses